The Mediating Effect of Electronic Word of Mouth (e-Wom) on Purchase Intention through Brand Image on Digital Platform - Istiqomah, Istiqomah; Fajri, Anisa (Economics and Business International Conference Proceeding, 2024)
The aim of this research is to find out how electronic word of mouth (e-WOM) influences purchase intention through brand image as a mediating variable. This research involved 100 respondents who were consumers of skincare X products. This research was conducted using sampling using non-probability sampling technique with purposive sampling type. The analysis technique in this research is path analysis using SmartPLS version 4.0. The results of the analysis show that the electronic word of mouth (e-WOM) variable (X) has a positive and significant effect on purchase intention (Y), the electronic word of mouth (e-WOM) variable (X) has a positive and significant effect on the brand image variable ( Z), the brand image variable (Z) has a positive and significant effect on purchase intention (Y), the brand image variable (Z) has a positive and significant effect and is able to mediate the electronic word of mouth (e-WOM) variable (X) on purchase intention (Y).